2, 2, 2-Trifluoroethanol activated one-pot Mannich-like reaction of β-nitroenamines, secondary amines, and aromatic aldehydes. Issue 25 (22nd June 2016) - Han, Li; Feng, Yian; Luo, Ming; Yuan, Zihao; Shao, Xusheng; Xu, Xiaoyong; Li, Zhong
Graphical abstract: Highlights: A unique and efficient one-pot reaction of β-nitroenamines, secondary amines, and aromatic aldehydes. 2, 2, 2-Trifluoroethanol (TFEA) was used to activate this reaction. Afford the desired Mannich-like products in moderate to excellent yields with wide substrate scopes. Abstract: A unique and efficient 2, 2, 2-trifluoroethanol-activated one-pot reaction of β-nitroenamines, secondary amines and aromatic aldehydes was developed under mild and convenient conditions. In the presence of 2, 2, 2-trifluoroethanol (TFEA), aromatic aldehydes were activated by hydrogen bonding with TFEA. The newly-developed reaction could afford the desired Mannich-like products in moderate to excellent yields with wide substrate scopes.